PERAN INTERNATIONAL LABOUR ORGANIZATION DALAM MENDORONG INDONESIA UNTUK MELINDUNGI PEKERJA PLATFORM DIGITAL PADA MASA PANDEMI (2020-2022) - Refaldiansyah, Surya; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Digital platform workers, seeking employment or income through applications or websites, have significantly altered the labor market structure with unique characteristics such as flexibility, mobility, and diversity. Despite offering freedom, digital platform workers also face serious challenges, including job uncertainty, discrimination, and a lack of social protection. These conditions have been further exacerbated by the COVID-19 pandemic, impacting digital platform workers across various aspects, ranging from health to economic and social stability. However, there is currently no specific policy regarding the protection of these workers. This research employed a qualitative method with a case study approach to collect and analyze data from both primary and secondary sources. Primary data is obtained through direct interviews with representatives from ILO Indonesia-Timor Leste, representatives from the Ministry of Manpower of the Republic of Indonesia, and representatives from Labor Unions affected by the pandemic. Secondary data is sourced from conventions, documents, reports, articles, and other forms of information. The research shows that the ILO influences the landscape of Indonesia's labor policy regarding the protection of digital platform workers by providing in-depth understanding, advocating for improved social guarantees, and enhancing skills through an inclusive approach. The ILO implements diverse programs and activities, including research, training, workshops, conferences, advocacy, and networking, to raise awareness, build capacity, and engage the Indonesian government in safeguarding digital platform workers during the pandemic. Close collaboration with the government, workers, employers, and other organizations is also a focus of the ILO to develop policies and standards. Keywords: Protection, digital platform workers, ILO, pandemic, COVID-19, Indonesia, Labour Unions.